An investigation into the soft skills required of potential building graduate employee for sustainable employment - Ojo; Samson Abayomi; E A O, Anaele; H O, Omeje (Journal of Management and Science, 2022)
This study investigated the soft skills that Building Technology Students need for sustainable employment in Building Construction Industry. The study answered four research questions and tested four null hypotheses at 0.05 level of significance. The study adopted descriptive survey research design and was carried out in South-West, Nigeria. The population for the study was of 197 comprising of 159 employers from registered building construction industry and 38 building technology teachers from Building Technology Department in Polytechnics in South-West, Nigeria. There was no sampling for the study since the entire population was used. The instrument that was used for collecting data for the study was a structured questionnaire. The questionnaire was divided into two parts, I and II. Part I contains items that elicited the demographic information of the respondents while part II contains 62 soft skills items in four sections (A, B, C and D) on a five point likert-type rating scale option of Extremely Needed (EN),Somewhat Needed (SN), Neither Needed or Not Needed (NN), Somewhat Not Needed (SN) and Extremely Not Needed (EN) with a corresponding value of 5, 4, 3, 2 and 1 respectively. The face validation of the instrument was carried out by five experts. The Cronbach alpha coefficient (∝) method was used to ascertain the internal consistency of the questionnaire items and it yielded an overall reliability coefficient of 0.88. Data generated from the administration of the questionnaire was analyzed with Statistical Package for Social Sciences (SPSS) using mean and t-test statistics to answer the research questions and hypotheses respectively at 0.05 level of significance. Findings revealed that personal-attribute skills, people-related skills, higher-order thinking skills and career-attribute skills are required by building technology students in Polytechnics for sustainable employment in building construction industry. Based on the findings of the study, appropriate conclusions and recommendations were made which include the integration of the identified soft skills into the curriculum of building technology programme in Polytechnic among others.